2019
DOI: 10.1111/ner.12927
|View full text |Cite
|
Sign up to set email alerts
|

Chronic electrical stimulation reduces hyperalgesia and associated spinal changes induced by peripheral nerve injury

Abstract: Objectives We aimed to investigate if different protocols of electrical stimulation following nerve injury might improve neuropathic pain outcomes and modify associated plastic changes at the spinal cord level. Materials and Methods Adult rats were subjected to sciatic nerve transection and repair, and distributed in four groups: untreated (SNTR, n = 12), repeated acute electrical stimulation (rAES, 50 Hz, one hour, n = 12), chronic electrical stimulation (CES, 50 Hz, one hour, n = 12), and increasing‐frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…All results suggest that downregulation of KCC 2 after PNI plays an essential role in the development of NP [17]. Many studies have found that increasing the expression of KCC 2 significantly relieves NP behavior [9,[18][19][20]. Therefore, learning how to increase the expression of KCC 2 following PNI has great potential value for treating NP.…”
Section: Introductionmentioning
confidence: 87%
“…All results suggest that downregulation of KCC 2 after PNI plays an essential role in the development of NP [17]. Many studies have found that increasing the expression of KCC 2 significantly relieves NP behavior [9,[18][19][20]. Therefore, learning how to increase the expression of KCC 2 following PNI has great potential value for treating NP.…”
Section: Introductionmentioning
confidence: 87%
“…Mechanical withdrawal threshold (MWT) was determined by the same experimenter at 12 weeks after SNT induction using the BEM-404 mechanical analgesia tester [Chinese Academy of Medical Sciences (CAMS), Beijing, China] [21]-the cutoff force was set at 50 g. A rigid tip was applied perpendicularly to the medialplantar surface of the hind paw [29]. Brisk withdrawal or paw flinching was considered a positive response.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…In animals that respond to SCS, a significant increase of GAD 65 was observed in superficial dorsal horn, probably reflecting an increased GABA production following SCS. Recently, López-Álvarez et al (11) used a rat model of sciatic nerve transection and repair to show that chronic stimulation protocols restored the amount of KCC2, which had been significantly decreased by nerve injury, in the dorsal horn of these rats.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%